1975
DOI: 10.1017/s004317450006255x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Enrichment Studies with Trifluralin

Abstract: Soil enrichment studies were conducted with trifluralin (α,α,α-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine) with and without exogenous carbon and nitrogen. From 72 bacterial isolates obtained, eight representative ones were tentatively identified as members of the genusPseudomonasbased on size, shape, Gram reaction, and reaction on fluorescent and motility agar. Two of these eight isolates exhibited a significant increase in numbers of viable cells when grown in a medium with trifluralin as the only exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…were shown to be capable of degrading trifluralin and other dinitroaniline herbicides. Carter and Camper (1975) also identified eight isolates of Pseudomonas sp. among 72 bacterial isolates from a trifluralin-enriched soil.…”
Section: Biologicavchemical Transfonnationsmentioning
confidence: 99%
“…were shown to be capable of degrading trifluralin and other dinitroaniline herbicides. Carter and Camper (1975) also identified eight isolates of Pseudomonas sp. among 72 bacterial isolates from a trifluralin-enriched soil.…”
Section: Biologicavchemical Transfonnationsmentioning
confidence: 99%
“…Golab et al 23 noted a low level of mineralization in the field; they identified the intermediate products of degradation under these conditions and suggested a scheme for the catabolism of trifluralin. A few other publications have described the growth of bacterial isolates in media containing trifluralin under aerobic conditions and identified some of the same degradation products 8–11. The initial reactions suggested by Golab et al 23 are N ‐dealkylation of the propyl group producing TR‐2, replacement of the substituted amino group by a hydroxyl, forming TR‐20, monohydroxylation of the aromatic ring and of the propyl group producing TR‐36 and TR‐41 respectively, and reduction of the nitro group to an amine, forming TR‐4 (Fig 3).…”
Section: Resultsmentioning
confidence: 94%
“…Trifluralin (α,α,α‐trifluoro‐2,6‐dinitro‐ N,N ‐dipropyl‐ p ‐toluidine) is a dinitroaniline compound which was first produced in the 1960s and has been used extensively as an agricultural herbicide. There is little information on the biodegradation of this compound by pure bacterial isolates8–11 and to our knowledge no work has been done on the genetic aspects of the catabolism of this molecule. In this article, we report the analysis of DNA isolated from bacteria shown to degrade trifluralin, using as probes the catabolic genes ndoB, todC1 and xylX , which encode the enzymes naphthalene 1,2‐dioxygenase,12 toluene dioxygenase13 and toluate 1,2‐dioxygenase14 respectively (enzymes that prepare the aromatic ring for the cleavage step), in addition to the genes catA and xylE , which encode catechol 1,2‐dioxygenase15 and catechol 2,3‐dioxygenase16 (the ring‐cleaving enzymes), respectively (Fig 1).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Although there has been considerable research on the degradation of trifluralin in soil, few studies have reported degradation by isolated microorganisms, a necessary pre-requisite if the microbial enzymes and pathways involved are to be discovered. [10] It was proven in another recent study [11,12] that a species of Pseudomonas was responsible for decomposing trifluralin. Degradation in nonsterilized soil is more than sterilized soil.…”
Section: Introductionmentioning
confidence: 99%